Evaluation of Expectations and Quality Health Care Based on Patients’ Perspectives in Universitas Gadjah Mada Academic Hospital - Sugiarsih Sugiarsih (Academic Hospital Journal, 2018)
Background: Health services provided by hospitals can be used as capital to improve the image of services and compete with other hospitals in order to be the patients’ preferred choice in solving their health problems. Patients have different perceptions of medical services provided which can be used for describing the quality of hospital services.Methods: This research was a descriptive analytic study with a cross-sectional design, where data retrieval used a questionnaire which measures the patients’ expectations and perceptions of services from the Outpatient, Inpatient and Emergency Departments with 5 dimensions of quality: tangibles, responsiveness, empathy, reliability and assurance. The study population was patients who visited the outpatient, inpatient and emergency departments totaling 5000 samples as calculated by the Slovin formula, with a sample set of 120 respondents selected by random sampling. Data were analyzed using independent sample t tests to determine differences in patients’ expectations and perceptions of services obtained at the time of visit. ANOVA tests were used to analyze data about differences in patients’ expectations and perceptions of the outpatient, inpatient and ER departments. For the descriptive study, the data were analyzed by finding the average of the patients’ responses. Results: Patient expectations of service quality was an important quality dimension which reached an average value of 93.97. The perception of the quality of services reached a value of 84.12. Statistically, there was no difference between the quality of the outpatient, emergency and inpatient departments with p=0.4 (>0.05). There was a statistically significant difference in patient expectations and perceptions of service quality delivered both with p=0.000 (<0.05). Conclusions: According to the perceptions of patients, quality of service at the Universitas Gadjah Mada Hospital is excellent. There was no difference between the quality of service in the outpatient, emergency and inpatient units. There were statistically significant differences between patient expectations and perceptions of service quality.